Effects of bilateral dorsolateral prefrontal cortex high-definition transcania direct-current stimulation on physiological and performance responses at severe-intensity exercise domain in elite road cyclists - Gallo, G.; Geda. E.; Codella, R.; Faelli, E.; Panascì, M.; Ranieri, L. E.; Pollastri, L.; Brighenti, S.; Molino, L.; Riba, U.; Luzi, L.; Ruggeri, P.; et al. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To investigate the effects of bilateral dorsolateral prefrontal cortex high-definition transcranial direct-current stimulation (HD-tDCS) on physiological and performance responses during exercise at the upper limit of the severe-intensity exercise domain in elite-level road cyclists. Methods: Eleven elite-level road cyclists (VO2peak: 71.8 [3.1] mL·kg-1·min-1) underwent the HD-tDCS or SHAM condition in a double-blind, counterbalanced, and randomized order. After 20 minutes of receiving either HD-tDCS on dorsolateral prefrontal cortex (F3 and F4) or SHAM stimulation, participants completed a 10-minute constant-load trial (CLT1) at 90% of the first ventilatory threshold and a 2-minute CLT (CLT2) at peak power output. Thereafter, they performed a simulated 2-km time trial (TT). Maximal oxygen uptake, respiratory exchange ratio, heart rate, and rating of perceived exertion were recorded during CLT1 and CLT2, whereas performance parameters were recorded during the TT. Results: In 6 out of 11 cyclists, the total time to complete the TT was 3.0% faster in HD-tDCS compared to SHAM. Physiological and perceptual variables measured during CLT1 and CLT2 did not change between HD-tDCS and SHAM. Conclusions: HD-tDCS over the dorsolateral prefrontal cortex seemed to improve cycling TT performance within the upper limit of the severe-intensity exercise domain, suggesting that an upregulation of the prefrontal cortex could be critical even in this exercise intensity domain. However, the limited dimension and the high interindividual variability require further studies to test these putative ergogenic effects.